Improvement of the nutritional quality of lentil flours by infrared heating of seeds varying in size. (1st December 2022) - Liu, Siyuan; Ren, Yikai; Yin, Hanyue; Nickerson, Michael; Pickard, Mark; Ai, Yongfeng
Graphical abstract: Highlights: Infrared heating enhanced starch digestibility of lentil flours via gelatinization. Infrared treatment increased protein digestibility and quality of lentil flours. Infrared heating converted some insoluble dietary fiber to soluble in lentil flours. Infrared treatment decomposed heat-labile Vitamins B1, B3, and B9 in lentil flours. Processing variables affected starch digestibility but not other examined nutrients. Abstract: The present study aimed to tackle research gaps regarding how infrared heating affected macro- and micronutrients of lentil flours from seeds varying in size. Infrared treatments reduced resistant starch contents of lentil flours from 26.1–33.6% to 6.0–17.8%, increased protein digestibility from 73.6–75.0% to 78.2–82.2%, and enhanced soluble dietary fiber contents from 6.1–7.8% to 7.4–10.3%. Infrared treatments did not alter the primary limiting amino acid of Greenstar and Imvincible lentil flours (tryptophan) but changed that of Maxim to methionine + cysteine at 150 °C heating. Regarding micronutrients, the thermal modifications decreased the levels of heat-labile B vitamins, including B1 (thiamine), B3 (niacin), and B9 (mainly 5-methylterahydrofolate), consistent with reducing α-amylase activity to an undetectable level in all the three lentil flours. The novel findings from this research will be meaningful for the agri-food industry to utilize infrared processing as an effective and clean-label approach to improving the nutritional profiles of lentil and other flours.